2022
DOI: 10.3389/fmicb.2022.820569
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cecal Microbiota and Performance Indices Between Lean-Type and Fatty-Type Pekin Ducks

Abstract: Fatty-type (FT) Pekin ducks exhibit higher lipid deposition than lean-type (LT) ducks. The gut microbiota plays an important role in modulating fat metabolism. We compared the growth performance, slaughter performance, and cecal microbiota of FT and LT Pekin ducks and analyzed the role of cecal microbiota in lipid deposition in Pekin ducks. A total of 140 1-day-old FT and LT Pekin ducks with similar body weights were randomly assigned to 10 cages, with 14 ducks in each replicate. All ducks were fed commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Relative abundances of Firmicutes, Bacteroidetes, Tenericutes, and Proteobacteria increased significantly in DLW, CLW, BLW, and ALW groups than in the other groups (p < 0.001, p < 0.001, p = 0.002, and p = 0.001, respectively). Spirochaetes were closely associated with fat metabolism pathways (Yang et al, 2022) and can degrade pectin and xylan (Liu et al, 2014;Tokuda et al, 2018). Spirochaetes was the dominant bacteria in this study, but the difference in relative abundance between groups was not significant.…”
Section: Discussionmentioning
confidence: 53%
“…Relative abundances of Firmicutes, Bacteroidetes, Tenericutes, and Proteobacteria increased significantly in DLW, CLW, BLW, and ALW groups than in the other groups (p < 0.001, p < 0.001, p = 0.002, and p = 0.001, respectively). Spirochaetes were closely associated with fat metabolism pathways (Yang et al, 2022) and can degrade pectin and xylan (Liu et al, 2014;Tokuda et al, 2018). Spirochaetes was the dominant bacteria in this study, but the difference in relative abundance between groups was not significant.…”
Section: Discussionmentioning
confidence: 53%
“…The abundance of Anaerobiospirillum was significantly positively correlated with Norsanguinarine, (3-[4-[2-3.5,7trihydroxy-6-3,4-dihydro-2H-1-benzopyran-2-yllphenyl) oxidanesulfonic acid, (−)-11-hydroxy-9,10-dihydrojasmonic acid 11-beta-Dglucoside and (4-{2-hexatriaconta-16,24,26,28-tetraen-12-yl] propyl}-2-hydroxycyclohexyl) oxidanesulfonic acid Dextrin D-Ribose. Anaerobiospirillum may reduce fat deposition (Li et al, 2022), and studies have found that it is significantly enriched in the cecum of lean ducks compared to Peking ducks (Yang et al, 2022). Lactobacillus can improve the feed efficiency of chickens (Gao et al,FIGURE 6 The rectal metabolomics pathway of two groups of laying ducks with different residual feed intake was analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that the abundance of Megamonas in male chickens was significantly positively correlated with glycogen phosphorylase L ( PYGL ) expression in the cecum ( Cui et al, 2021 ), and the PYGL gene was involved in glycan metabolism. Compared to fatty-type ( FT ) Pekin ducks, Anaerobiospirillum has significantly enriched in the cecum of lean-type ( LT ) ducks ( Yang et al, 2022 ). In this study, we also found that the relative abundance of Megamonas (R = −0.52 and R = −0.51) and Anaerobiospirillum (R = −0.58 and R = −0.60) were significantly negatively correlated with abdominal fat weight and relative abdominal fat weight ( P < 0.01).…”
Section: Discussionmentioning
confidence: 99%